Pulau Dokdo menerusi perspektif Korea Selatan: Cabaran kedaulatan, pembangunan ekonomi dan penyelesaian konflik / Azlie Ismail - Azlie , Ismail (2019)
This study analyzes the Dokdo conflict from a South Korean perspective. It relates to the sentiment of nationalism, national identity and the development of the South Korean nation state. The issue became a territorial dispute when Japan also claimed the island by calling it Takeshima. Conflict towards the ownership of Dokdo began after the end of the Second World War when the 1951 San Francisco Peace Treaty failed to clarify the actual status of the island. For South Korea, Dokdo is part of its territory even though it was annexed by Japan in 1905. Seoul insists that there is no territorial dispute with Tokyo. Thus, this study concentrates on how South Korea reinforces its control over Dokdo. The history of Japanese colonialism on the Korean Peninsula directly contributes to the enhancement of nationalism as well as the strengthening of the South Korean national identity. The sentiment of nationalism is often used in justifying South Korean rights and sovereignty over Dokdo. This is discussed through the Geo-Body theory proposed by Tongchai Winichakul, an academic from Thailand. The study found that nationalism and national identity have become the basis of holding on to Dokdo. This is because the island is part of the South Korean Geo-Body. The collective memory of the South Korean community is filled with memorabilia of Dokdo in their daily lives, which in turn strengthens the nation state. In strengthening its ownership, South Korea carries out various activities including developing economic activities and conserving the environment on Dokdo. In doing so, South Korea not only maintains its effective control of Dokdo but also strengthens its Geo-body. Finally, the researcher provides some suggestions to minimize the conflict since settlement has not yet been reached. The involvement of various parties such as international organizations and the role of the United States is discussed in minimizing the tensions inherent between Seoul and Tokyo. By minimizing tensions, it is expected that South Korea will continue to strengthen its national identity and nation without any interferences. Keywords: South Korea, Dokdo, Geo-Body, Nationalism, Japanese Colonialism, San Francisco Peace Treaty 1951